ALK Inhibitors or Chemotherapy for Third Line in ALK-positive NSCLC? Real-world Data. (28th January 2022) - Moskovitz, Mor; Dudnik, Elizabeth; Shamai, Sivan; Rotenberg, Yakir; Popovich-Hadari, Noa; Wollner, Mira; Zer, Alona; Gottfried, Maya; Mishaeli, Moshe; Rosenberg, Shoshana Keren; Onn, Amir; Merimsky, Ofer; et al.
Abstract: Objectives: ALK inhibitors (ALKi) are the standard-of-care treatment for metastatic ALK-rearranged non-small cell lung cancer (NSCLC) in the first- and second-line setting. We conducted a real-world multi-institutional analysis, aiming to compare the efficacy of third-line ALKi versus chemotherapy in these patients. Methods: Consecutive ALK-positive metastatic NSCLC patients treated with at least one ALKi were identified in the working databases of 7 Israeli oncology centers (the full cohort). Demographic and clinical data were collected. Patients receiving any systemic treatment beyond 2 ALKi comprised the third-line cohort, whether a third ALKi (group A) or chemotherapy (group B). Groups A and B were compared in terms of overall survival (OS) and time-to-next-treatment line (TNT). Results: At a median follow-up of 41 months (95% confidence interval [CI]: 32-55), 80 (47.1%) have died. Median OS (mOS) in the full cohort ( n = 170) was 52 months (95% CI: 32-65). Number of ALKi (hazard ratio [HR] 0.765; 95% CI: 0.61-0.95; P = .024) and age (HR 1.02, 95% CI: 1.01-1.04, P = .009) significantly associated with OS in the full cohort. The third-line cohort included 40 patients, of which 27 were treated with third ALKi (group A) and 13 treated with chemotherapy (group B). mOS from third-line initiation was 27 months in group A (95% CI: 13-NR) and 13 months for group B (95% CI: 3-NR); the difference was not significant (NS; P = .12). Chemotherapy as first line (HR 0.17, 95% CI: 0.05-0.52, P = .002) and a higher number of ALKi (HR 0.38, 95% CI: 0.20-0.86, P = .011) associated significantly with longer OS of the third-line cohort. TNT was 10 months for group A (95% CI: 5-19) and 3 months for group B (95% CI: 0-NR); the difference was NS ( P = .079). Conclusion: We report mature real-world data of more than 4-year mOS in ALK-positive patients. The number of ALKi given was associated with a better outcome. OS and TNT demonstrated a statistically nonsignificant trend for a better outcome in patients receiving a third-line ALKi. Abstract : ALK inhibitors are the standard-of-care treatment for metastatic ALK-rearranged non-small cell lung cancer in the first- and second-line setting. This article reports a real-world multi-institutional analysis, comparing the efficacy of third-line ALK inhibitors versus chemotherapy.